Search for photons above 10^18 eV with the hybrid detector of the Pierre Auger Observatory - Aab, A. (2017)
A search for ultra-high energy photons with energies above 1 EeV is performedusing nine years of data collected by the Pierre Auger Observatory in hybrid operation mode.An unprecedented separation power between photon and hadron primaries is achieved bycombining measurements of the longitudinal air-shower development with the particle contentat ground measured by the fluorescence and surface detectors, respectively. Only three photoncandidates at energies 1?2 EeV are found, which is compatible with the expected hadroninducedbackground. Upper limits on the integral flux of ultra-high energy photons of 0.027,0.009, 0.008, 0.008 and 0.007 km2 sr1 yr1 are derived at 95% C.L. for energy thresholds of1, 2, 3, 5 and 10 EeV. These limits bound the fractions of photons in the all-particle integralflux below 0.1%, 0.15%, 0.33%, 0.85% and 2.7%. For the first time the photon fraction at EeVenergies is constrained at the sub-percent level. The improved limits are below the flux ofdi↵use photons predicted by some astrophysical scenarios for cosmogenic photon production.The new results rule-out the early top-down modelsin which ultra-high energy cosmic raysare produced by, e.g., the decay of super-massive particlesand challenge the most recentsuper-heavy dark matter models.